Implementation of the utilization of PT Nestle's Corporate Social Responsibility (CSR) funds at public elementary school Srengsem 1 Bandar Lampung - Suryandari, Rani (Journal of Advanced Islamic Educational Management, 2021)
Corporate Social Responsibility (CSR) is a company's concern for the interests of other parties more broadly, not just the interests of the company itself. For companies that consistently implement CSR in their activities, in the long term they will benefit in the form of trust from their stakeholders. The purpose of this study was to determine the CSR contribution of PT Nestle Srengsem Bandar Lampung to education at the State Elementary School 1 Srengsem Bandar Lampung. The results of this study show that there are various types of company contributions, so PT Nestle in the field of education, namely the focus on nutrition, the focus on the environment and the focus on physical activity.